2002
DOI: 10.1007/bf03030429
|View full text |Cite
|
Sign up to set email alerts
|

NaCl stress causes changes in photosynthetic pigments, proteins, and other metabolic components in the leaves of a true mangrove,Bruguiera parviflora, in hydroponic cultures

Abstract: We studied salt stress-induced biochemical changes in young, hydroponically grown plants of mangrove, Bruguiera parviflora (Rhizophoraceae). Our focus was on the effect of NaCI (applied at 100, 200, 400, or 500 mM) on leaf pigments, total soluble proteins, total free amino acids, carbohydrates, polyphenols, and proline. The total Chl content increased for 14 d after treatment with 100 m/Vl NaCI, then gradually stabilized. At 400 mM, the total Chl content slowly decreased over the 45-d test period. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
148
4
13

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(175 citation statements)
references
References 42 publications
10
148
4
13
Order By: Relevance
“…Compatible solutes also include soluble carbohydrates, such as sugars (e.g. sucrose, glucose, fructose or trehalose), sugar alcohols (sorbitol, mannitol, as well as different inositol isomers and derivatives), and the raffinose family of oligosaccharides (Gavaghan et al, 2011;Parida et al, 2002). Although sugars have been shown to act as functional osmolytes in several species, it is not so easy to assess their specific functions in the responses to stress, which can be masked by their multiple additional roles as direct products of photosynthesis, components of the primary metabolism and regulatory molecules (Gil et al, 2013).…”
Section: Plant Growthmentioning
confidence: 99%
“…Compatible solutes also include soluble carbohydrates, such as sugars (e.g. sucrose, glucose, fructose or trehalose), sugar alcohols (sorbitol, mannitol, as well as different inositol isomers and derivatives), and the raffinose family of oligosaccharides (Gavaghan et al, 2011;Parida et al, 2002). Although sugars have been shown to act as functional osmolytes in several species, it is not so easy to assess their specific functions in the responses to stress, which can be masked by their multiple additional roles as direct products of photosynthesis, components of the primary metabolism and regulatory molecules (Gil et al, 2013).…”
Section: Plant Growthmentioning
confidence: 99%
“…9) in pI 6.9] were completely lost as a result of the NaCl treatment. Some researchers reported that the soluble protein contents with LMW, IMW and high molecular weight in leaves of different plant species decreased (Parida et al 2002) or increased (Elshintinawy and Elshourbagy 2001) in response to salinity. However, the changes in protein synthesis were determined as new synthesis, complete loss, increase and decrease (Yıldız 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Also, this case may be explained with an increase in activities of protein hydrolyzing enzymes during the NaCl stress treatment. Parida et al (2002) reported that the decrement in total soluble protein content of leaves as a result of the NaCl treatment might have resulted from an adverse effect of NaCl on the synthesis of certain LMW proteins. In addition, some researchers reported that the contents of two LMW proteins in hexaploid wheat, and 17 LMW and four IMW in tetraploid wheat decreased, while one LMW protein in hexaploid wheat and four LMW proteins in tetraploid wheat disappeared in the presence of NaCl (Elshintinawy andElshourbagy 2001, Yıldız 2007).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study indicated a strong role of arbuscular mycorrhizal symbiosis in enhancing stress tolerance in chickpea by significantly modulating proline metabolism and Na + uptake (Garg and Baher, 2013). The functions of other compatible solutes such as glucose and sucrose include osmotic adjustment, carbon storage and radical scavenging (Parida et al, 2002). Previous studies reported high levels of soluble sugar and proline accumulated in leaves of "Poncho Negro" tomato plants grown under salinity and excess B, but the increase was different depending on the salinity and B treatment (Contreras et al, 2011;Díaz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%